Ethnobotanical survey of medicinal and aromatic plants used by the population of Settat Province, Morocco - Manal Lahyaoui; Nadia Dakka; Naoual El Menyiy; Mansour Sobeh; Pakhrur Razi; Khang Wen Goh; Yaser Mohammed Al-Worafi; Muhammad Junaid Farrukh; Abdelhakim Bouyahya (Heliyon)
To promote Morocco's medicinal and aromatic plants, an ethnobotanical study was conducted in the Settat Province, part of the Casablanca-Settat region, Morocco. The methodology employed in this study involved a direct, oral survey conducted with 30 herbalists from various villages in the Settat province, after obtaining their informed consent. Additionally, an online survey was distributed, to which 212 individuals from the local population, representing different age groups, responded. The sample size was chosen to ensure a confidence level of 88 %. The results provided a database on the modes of use, plant parts utilized, treated pathologies, and recommended dosages for 51 medicinal and aromatic plants from the Settat province and enabled us to calculate their Familiarity Index (FI). The data collected showed that the Lamiaceae, Apiaceae, and Fabaceae families are the most represented. The calculated Familiarity Index indicated that the most commonly used species were Verbena, Pimpinella anisum L., and Origanum vulgare, with Familiarity Index of 0.22, 0.22, and 0.18, respectively. The most frequently utilized plant part was the leaves, and 70.59 % of respondents preferred drying the plants before preparing them as infusions or decoctions. The results highlighted the primary ailments treated with these plants, such as diabetes, gastrointestinal disorders, cardiovascular diseases, oral conditions, cancers, insomnia, and stress. Additionally, the study referenced traditional medicinal uses from various national studies and international scientific research that validated the therapeutic properties of each plant.